2017
DOI: 10.5455/ajvs.280407
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fermented Wheat Germ Extract on Biochemical, Physiological and Performance Parameters of Broiler Chickens

Abstract: Key words:Fermented Wheat Germ Extract, broiler, challenge Fermented wheat germ extract (FWGE) is a multisubstance composition contains 2-methoxy benzoquinone and 2, 6-dimethoxy benzoquinone which are likely to exert some of its biological effects as well as it is a concentrated source of vitamins, minerals, and protein.An experimental trial of FWGE supplementation to broiler feed from one day old with a rate of 0.5, 1.5 and 3 g/kg feed was tried. Results revealed that all doses of FWGE increased body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…In the present experiment, the results of blood constituents were in agreement with Ellakany et al (2017) who found the incorporation of fermented wheat germ extract with Saccharomyces cerevisiae at rates of 0.5, 1.5 and 3 g/kg diet significantly decreased triglyceride level in blood. A significant decrease in AST concentration was observed at a dose of 1.5 g//kg of diet, while both doses of 1.5 and 3 g/kg of diet decreased significantly ALT level in the blood.…”
Section: Meat Qualitysupporting
confidence: 92%
See 2 more Smart Citations
“…In the present experiment, the results of blood constituents were in agreement with Ellakany et al (2017) who found the incorporation of fermented wheat germ extract with Saccharomyces cerevisiae at rates of 0.5, 1.5 and 3 g/kg diet significantly decreased triglyceride level in blood. A significant decrease in AST concentration was observed at a dose of 1.5 g//kg of diet, while both doses of 1.5 and 3 g/kg of diet decreased significantly ALT level in the blood.…”
Section: Meat Qualitysupporting
confidence: 92%
“…On the other hand, Leeuw et al (2009) detected no difference in carcass weight and dressing percentage when using 75 or 100% maize germ meal in steers diets. Ellakany et al (2017) found that combination of fermented wheat germ extract with Saccharomyces cerevisiae at doses of 0.5, 1.5 and 3 g/kg of diet significantly increased the percentage of intestinal weight and decreased the weight of the liver and total body fat in broilers.…”
Section: Carcass Characteristicsmentioning
confidence: 95%
See 1 more Smart Citation
“…Three-week-old chickens were infected with Mycoplasma gallisepticum and treated with FWGE, and poultry remained clinically healthy [ 24 ]. In another research, FWGE was beneficial for the maintenance of general health conditions including biochemical and physiological parameters, increasing weight gain, and improved immune response to vaccination [ 25 ]. In growing pigs, FWGE enhanced weight gain and had a beneficial effect on cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Oil extracted from wheat germ can improve the damage of the liver and small intestine induced by carbon tetrachloride ( Saleh, 2016 ). Wheat germ fermentation products have also been proved to improve growth performance, carcass traits, and antibody titer of broiler chicks ( kany et al, 2017 ), and can effectively against the infection of Mycoplasma gallisepticum ( Stipkovits et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%